“Too Grey to Be True?” Sexual Violence in Older Adults: A Critical Interpretive Synthesis of Evidence - Anne Nobels (International Journal of Environmental Research and Public Health, 2020)
Sexual violence (SV) is an important public health issue with a major impact on victims and their peers, offspring and community. However, SV in older adults is under-researched. This paper aims to establish the prevalence and nature of SV in older adults in Europe, link this with existing policies and health care workers’ response to sexual health needs in older age, and critically revise the currently used frameworks in public health research. To fill this gap in the literature, we applied a Critical Interpretative Synthesis (CIS) approach. The CIS approach uses techniques from grounded theory and processes from systematic review. It allows to critically interpret key findings from both academic as well as grey literature, engendering theory refining. In the first phase of purposive sampling, we conducted a systematic review of academic sources and included 14 references. The cut-off age used to define old age varied between 60 and 70 years old among the included studies. Subsequently we added another 14 references in the second phase of theoretical sampling. We ultimately included 16 peer-reviewed articles and 12 documents from the grey literature. The CIS results demonstrate that knowledge of SV in older adults is still limited. The current research suggests that SV in older adults rarely occurs, however, prevalence rates are likely to be underestimated because of methodological shortcomings. The complexity of SV in older adults is not acknowledged in ongoing research due to the conflation of SV with other types of violence. Information on specific risk factors and about assailants committing SV in old age is absent. Policy documents dealing with sexual and reproductive health, rights and ageing make no mention of SV in older adults. In clinical practice, the sexual health needs of older adults often remain unmet. In conclusion, our findings suggest that older adults are forgotten in prevention and response to SV. Greater awareness about this topic could contribute to a revision of current policies and health care practices, leading to more tailored care for older victims of SV.